2015
DOI: 10.1071/hc15282
|View full text |Cite
|
Sign up to set email alerts
|

Priorities and approaches to investigating Asian youth health: perspectives of young Asian New Zealanders

Abstract: INTRODUCTION:The proportion of young people in New Zealand identifying with Asian ethnicities has increased considerably. Despite some prevalent health concerns, Asian youth are less likely than non-Asian peers to seek help. As preparatory research towards a more nuanced approach to service delivery and public policy, this qualitative study aimed to identify young Asian New Zealanders' perspectives on best approaches to investigate health issues of priority concern to them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 13 publications
0
22
1
Order By: Relevance
“…28,29 The stakeholders in this study discussed the importance of engaging young people in the research process over a period of time, enabling them to become familiar with the people with whom they share their views, a sentiment voiced by the young participants as well. 21 This is consistent with a growing body of knowledge supporting the benefits of hearing young people's voice in identifying their health issues and in developing appropriate solutions. [30][31][32] Although different methodologies are used in research with young people, participatory methodologies are increasingly employed.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…28,29 The stakeholders in this study discussed the importance of engaging young people in the research process over a period of time, enabling them to become familiar with the people with whom they share their views, a sentiment voiced by the young participants as well. 21 This is consistent with a growing body of knowledge supporting the benefits of hearing young people's voice in identifying their health issues and in developing appropriate solutions. [30][31][32] Although different methodologies are used in research with young people, participatory methodologies are increasingly employed.…”
Section: Discussionmentioning
confidence: 64%
“…23,24 The findings from this study are also broadly consistent with themes identified in a parallel study with similar objectives conducted among Asian youth. 21 In particular, young Asians advocated for and expressed a strong interest in engaging in health research addressing current barriers to accessing services. Both studies directly or indirectly highlighted challenges relating to cultural identity and issues around acculturation, difficulties in addressing mental health concerns, the importance of including parents in the discussion and the need for breaking down barriers and the unhelpful concept of the 'model minority' forced on young people and their families.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations